An exploration into the role of Narrative Therapy within educational psychology practice: a reflexive thematic analysis - Bradbury, Josephine (2023)
Aim: To explore how Narrative Therapy is construed and conceptualised by EPs; what implications this therapeutic approach raises for EP practice; how it can be delivered and to explore for whom this approach can best support.